DEVELOPED MATHEMATICAL TOOL FOR CO2 WAG AND HYDROCARBON IMMISCIBLE WAG INCREMENTAL RECOVERY PREDICTION FOR MEDIUM TO LIGHT OIL IN UNDERSATURATED RESERVOIRS - LAZREG, BELAZREG (2021)
Predicting the incremental recovery factor of an enhanced oil recovery (EOR) technique is a very crucial task.